Special Training Centre — An Initiative towards achieving the Goal of UEE in India - Singh, Ankit Kumar (THE PRIMARY TEACHER, 2016)
undamental Right for all children in the age group of 6–14 years in India. Therefore, they are entitled to free and compulsory education. The Right to Education (RTE) Act 2009 was implemented across the country on 1 April 2010, which is a part of the 86th Constitutional Amendment. The Sarva Shiksha Abhiyan (SSA) is a flagship programme of the Government of India in partnership with the States and Union Territories (UTs) to achieve the goal of Universalisation of Elementary Education (UEE). To achieve the target, i.e., to enrol all children in schools, special efforts must be made. As per the RTE Act 2009, Special Training Centres (STCs) were established in every school to provide out-of-school children with additional help to ensure that they are at par with other students. STCs become all the more important because as per the Act the children are to be admitted to classes according to their age. Just like a teacher is recruited in a school, a specialised teacher must be recruited in an STC to teach children with learning gaps. The enrolment of children in an STC becomes more effective with the community’s contribution. In order to establish these centres, rigorous work has been done by the SSA in Delhi. Moreover, nodal agencies have contributed to achieve UEE in all municipal schools in Delhi, Rajkiya Sarvodaya Bal Vidyalaya (RSBV), Rajkiya Sarvodaya Kanya Vidyalaya (RSKV), NGOs and madrasas